"It is now in your hands": South Africa"s dilemma for religion and governance in the changing COVID-19 context - Mpofu, Buhle (HTS teologiese studies, 2020)
This article examines how coronavirus disease 2019 (COVID-19) impacted on religion–state relations in South Africa. By examining the models of religion–state relations the article highlights the implications of these relations in the context of the South African government’s national response to COVID-19 and critically engages a public theology of ‘immense trust and authority’ assigned to leaders. The article identifies ‘separation with interaction’ as a model, which informs the South African government’s state–religion engagement. Although this model is constitutional and promotes religious freedom, the article identifies the government’s failure to act decisively on religious leaders who exploit the poor as a major obstacle to socio-economic and religious transformation. The article contends that the dark part of South African history presents a dilemma to church–state relations in South Africa and suggests that life-affirming practices of political and religious leaders should be tested through the values of goodness, kindness, justice and obedience as a demonstration that they are essential workers who have an important transformational role to play in the context of COVID-19.Contribution: This article represents a systematic and practical reflection within a paradigm in which the intersection of philosophy, religious studies, social sciences, humanities and natural sciences generates an interdisciplinary, multidisciplinary and transdisciplinary contested discourse.